Level of Under Passing Ability In Volleyball Games of Grade V Students of SD Inpres Salua (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of underhand passing ability in volleyball among fifth-grade students of SD Inpres Salua. Underhand passing is one of the most important basic techniques in volleyball because it functions to receive and control the first ball from the opponent's attack. The research method used is descriptive quantitative with an underhand passing skill test. Data were analyzed using descriptive statistics in the form of frequency distributions and percentages, then classified into the categories of Very Good, Good, Sufficient, Less, and Very Less. The results showed that of the 25 students sampled, the majority were in the "Sufficient" category (56.00%), followed by the "Less" category (40.00%), and only a small portion were in the "Very Good" category (4.00%). There were no students in the "Good" or "Very Less" categories. This finding indicates that although students have understood the basic techniques of underhand passing, their consistency and accuracy are still lacking. The conclusion of this study is that the underhand passing ability of fifth-grade students of SD Inpres Salua is mostly still at an intermediate level. The research recommendations are the need for intensified training with drill methods, variations in training forms, and regular evaluations so that underhand passing skills can improve significantly.